2000
DOI: 10.2166/wst.2000.0052
|View full text |Cite
|
Sign up to set email alerts
|

Biological hydrogen potential of materials characteristic of the organic fraction of municipal solid wastes

Abstract: The purpose of this study is to investigate the biological hydrogen production potential of individual organic fraction of municipal solid wastes (OFMSW) by batch experiments. Seven varieties of typical organic solid wastes including rice, cabbage, carrot, egg, lean meat, fat and chicken skin were selected to estimate the hydrogen production potential. Among the OFMSW, carbohydrate produced the most hydrogen through biological hydrogen fermentation compared with proteins or lipids. Subsequently, the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
1
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(113 citation statements)
references
References 0 publications
13
90
1
9
Order By: Relevance
“…These wastes are complimentary for biological hydrogen production. FW collected from dining hall contains a variety of beans and vegetables like rice, wheat bran, potatoes, pulse, cabbage, beans and peas [18][19]23,29]. The maximum content of carbohydrates makes FW an auxiliary feedstock for the production of biohydrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These wastes are complimentary for biological hydrogen production. FW collected from dining hall contains a variety of beans and vegetables like rice, wheat bran, potatoes, pulse, cabbage, beans and peas [18][19]23,29]. The maximum content of carbohydrates makes FW an auxiliary feedstock for the production of biohydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Co-digestion of FW with sewage sludge produces biohydrogen because FW and SS were known as necessary and auxiliary substrate for hydrogen production. Some experimental results were reported using food waste [13,[18][19][20], waste activated sludge [21][22], municipal solid waste [18,[23][24][25]. FW is suitable for the production of hydrogen as it is rich in carbohydrate and hydrolyzable waste [26].…”
Section: Introductionmentioning
confidence: 99%
“…This has driven humanity into looking for alternative sources of fuel that will not endanger the environment when used or combusted. A study by Mizuno et al (2000) showed that hydrogen has a high energy content (122 kJ/g), the combustion produces water which does not endanger the environment and it is environmentally friendly. Okamoto et al (2000) reported that out of the various processes of producing hydrogen such as steam reforming, electrolysis, gasification and biological processes, the least expensive process is the biological process, which uses organic components of waste as resources.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used heat treatment of the inoculum used to seed the reactors as a method to inactivate or eliminate these microorganisms. Lay (2000) and Okamoto (2000) used wet heat treatment (boiling for 15 minutes) of anaerobic digester sludge, whereas Van Ginkel et al (2001) used dry heat treatment (baking at 104 °C for 2 hours) of compost and soils. The motivation for this heat treatment is to inactivate hydrogen consuming microorganisms and to select for hydrogen producing bacteria.…”
Section: Introductionmentioning
confidence: 99%